A Novel QR Code Watermarking In Digital Media Using DWT (International Journal of Engineering and Computer Science, 2014)
Due to the extensive use of digital media applications, multimedia security and copyright protection has gained tremendous importance. Digital Watermarking is a technology used for the copyright protection of digital applications. In this project, a comprehensive approach for watermarking digital QR code image is introduced. We propose a hybrid digital media watermarking scheme based on Discrete Wavelet Transform (DWT) for a digital invisible watermarking is to embed binary image in the QR code image. In our method we embed a binary image considered as watermark embedded into one of selected wavelet subband. The proposed algorithm is also implemented on videos which is a novel approach compared to previous works based on the images. The experimental results show that our method has more robustness to attacks in different considerations and it can achieve a viable copyright protection and authentication.